PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KONSERVATISME AKUNTANSI PADA PERBANKAN YANG TERDAFTAR DI BURSA EFE - Baihaqi Ammy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
This research aims to prove whether there was an effect of good corporate governance mechanisms (GCG) in this regard include the board of directors, commissioners, komitea auditing, and accounting conservatism institutional ownership in banks listed on the Indonesia Stock Exchange (IDX) in the period 2010 to 2013. This research is associative causal research. Sampling technique used was saturated sampling (census). The data used are secondary data from the financial statements of banking companies listed in Indonesia Stock Exchange (IDX) obtained through the website www.idx.co.id. This data will be analyzed using multiple linear regression analysis method, which method is descriptive statistical methods used to analyze the data more than two variables of the study. The classical assumption used is the normality test, multicollinearity, heteroscedasticity test, and autocorrelation. Testing hypothesis is t - test, test - F, and the coefficient of determination (R2). This research resulted in four discoveries as has been proposed in the research hypothesis. First, the board of directors variables significantly effect accounting conservatism. Second, the variable commissioners significantly effect accounting conservatism. Third, the audit committee variables significantly effect accounting conservatism. Fourth, institutional ownership variables significantly effect accounting conservatism.